An Exegetical Exploration of the Concept of ‘Training’ in the Book of proverbs (2014)
Training, a generic word for the process of perfecting a specific skill or purpose, encapsulates the rationale for parenting in the book of Proverbs 22:6. However, existing interpretations of the Hebrew ḥănōḵ (train) in the cited text limit it to the disposition, manner, morality and choice of vocation for adolescents while infant nurturing; a more foundational stage in parenting, has been ignored. Consequently, the study analysed Proverbs 22:6 to appropriately situate the necessity, meaning, timing, parental roles, and relevance of nurturing during infancy as a fundamental component of training as prescribed in the selected text.The study adopted John Bowlby‘s Attachment theory which emphasises the impact of parent–infant attachment on the child‘s personality and character formation. The concise Proverbs 22:6 is selected because of the centrality of ḥănōḵ in the process of infant nurturing. The Historical-Grammatical Method which examines the socio-cultural and grammatical structure of a text was utilised in the exegesis of Proverbs 22:6 and its interpretation.The use of ḥănōḵ in its imperative form in Proverbs 22:6 suggests the necessity of training in parenting which aims at averting the adverse effects of parental negligence and irresponsibility.Popular interpretations, which adopt Proverbs as a ‗royal text‘, limit ḥănōḵ to ‗initiating a cadet into the military‘, ‗vocational training‘, ‗preparation for royalty‘, ‗developing a child‘s nature or disposition‘ or ‗exposure to godly rules and principles for living‘, when linked with lanna`ar ‗the child‘ and darKô ‗his way‘. However, from the covenantal viewpoint of which the family is central, ḥănōḵ is appropriately rendered as ‗wholistic training‘ which encompasses nurturing, teaching, discipling, modeling, and disciplining the child in every aspect of life (morally, mentally, emotionally, and economically) from infancy until maturity. Etymologically, ḥănōḵ depicts a mother engaged in the nurturing of an infant by rubbing jam on his gums to stimulate desire.This has dual implications. First, it underscores the timing of‗training‘ (at infancy) because, when parents are addressed, the object of ‗training‘ is predominantly the unborn or an infant, invalidating such renderings of lanna`ar as ‗adolescent‘, ‗squire‘, or ‗cadet‘. Second, it explicates mothers‘ weighty role in establishing attachment and character formation, fundamental in wholistic training. Nevertheless, wholistic training requires joint parental commitment to engage quality time, skill and means. The parallel between lanna`ar in Proverbs 22:6a and zaqen ‗old age‘ in 22:6b accentuates the enduring nature of wholistic training because, when zaqen sets in, people retire from certain vocations or services, yet normal life continues.Therefore, although freedom of choice makes derailment probable, wholistic training, of which nurturing during infancy is foundational, can be remedial.